Structure of the DNA‐binding domain of the response regulator SaeR from Staphylococcus aureus. (1st August 2015) - Fan, Xiaojiao; Zhang, Xu; Zhu, Yuwei; Niu, Liwen; Teng, Maikun; Sun, Baolin; Li, Xu
<x xml:space="preserve">Abstract</x> The SaeR/S two‐component regulatory system is essential for controlling the expression of many virulence factors in Staphylococcus aureus. SaeR, a member of the OmpR/PhoB family, is a response regulator with an N‐terminal regulatory domain and a C‐terminal DNA‐binding domain. In order to elucidate how SaeR binds to the promoter regions of target genes, the crystal structure of the DNA‐binding domain of SaeR (SaeRDBD) was solved at 2.5 Å resolution. The structure reveals that SaeRDBD exists as a monomer and has the canonical winged helix–turn–helix module. EMSA experiments suggested that full‐length SaeR can bind to the P1 promoter and that the binding affinity is higher than that of its C‐terminal DNA‐binding domain. Five key residues on the winged helix–turn–helix module were verified to be important for binding to the P1 promoter in vitro and for the physiological function of SaeR in vivo.